Optimasi Optimasi Minyak Daging Buah Pala dengan Response Surface Methodology (RSM): Optimasi Minyak Daging Buah Pala dengan Response Surface Methodology (RSM) - Nirmagusitna, Dwi Eva; Putri Andini, Mutia Merry; Wulandari, Yeni Ria (Jurnal Penelitian Pertanian Terapan, 2024)
Nutmeg flesh is the largest part of the nutmeg (77.8%) and can be used to produce nutmeg oil. The purposa of study is to determine the approproate distillation temperature and time to produce optimal yield of nutmeg flesh oil, to determine variations in temperature and distillation time based on Response Surface Methodology (RSM) with the optimal percentage of nutmeg flesh oil yield and requirement SNI nutmeg oil and to determine the content chemical compound in nutmeg flesh oil. The study was conducted in two stages. The first stage, optimizing the distillation process using RSM with a Central Composite Design (CCD) design. The second stage, making nutmeg flesh oil. The best sample of nutmeg flesh oil is the distillation temperature and time (95ºC, 4.5 hours) with yield (0.73%), specific gravity (0.91 g/ml), refractive index (1.4932), and solubility in ethanol 90% (20.00%). The results of GC-MS analysis of nutmeg flesh oil showed that the myristicin content require the SNI (35.30%). The variations of distillation temperature and distillation time suggested by CCD Design is 95ºC for 5.5 hours with results, yield (0.71%), specific gravity (0.882 g/ml), refractive index (1.485), and solubility in ethanol 90% (16.67%). The results of the analysis require the quality standards of nutmeg oil (SNI 06-2388-2006).